Childhood trauma and adult declarative memory performance in the general population: The mediating effect of alexithymia. (March 2020) - Terock, Jan; Van der Auwera, Sandra; Janowitz, Deborah; Wittfeld, Katharina; Frenzel, Stefan; Klinger-König, Johanna; Grabe, Hans J.
Abstract: Background: Previous studies suggested that childhood maltreatment is associated with altered memory performance in adulthood. Deficits in identifying and describing feelings as captured by the alexithymia construct are strongly linked with childhood trauma and may mediate the associations with memory function. Objective: To investigate the associations of childhood trauma with verbal declarative memory performance and the putative mediating role of alexithymia. Method: Associations of the different dimensions of childhood trauma with adult declarative memory performance were tested in two large, independent general population samples comprising a total of N = 5574 participants. Moreover, we tested whether associations were mediated by alexithymia. Results: In both samples, childhood emotional neglect, but not abuse emerged as a negative statistical predictor of early (sample 1: β=-1.79; p < 0.001, sample 2: β=-0.26; p < 0.001) as well as delayed recall (β=-0.78; p < 0.001; β=-0.24; p < 0.05). Likewise, childhood emotional neglect was the strongest predictor for alexithymia (β = 3.2; p < 0.001; β = 3.54; p < 0.001). Finally, the association between childhood emotional neglect and early (Total Mediated Effect (TME): 13.2, CI: 0.087-0.302; TME: 20.1; CI: 0.123-0.619) as well as late recall (TME: 13.2, CI: 0.086-0.301; TME: 9; CI: -0.442-0.699) was significantly mediated by alexithymia. Conclusions: Our findings suggest that childhood emotional neglect is particularly detrimental to memory functioning in adulthood. In comparison, childhood abuse was not associated with reduced declarative memory capacity. Our results contribute to explain the mechanism underlying the relation of childhood trauma and memory deficits: Finding specific associations with emotional neglect and a mediating role of alexithymia highlights the relevance of emotion processing capacities for memory functioning.